Application of Real-Time Automated Traffic Incident Response Plan Management System: A Web Structure for the Regional Highway Network in China. (16th November 2014) - Ma, Yongfeng; Zhang, Wenbo; Xie, Junping; Lu, Jian
Abstract : Traffic incidents, caused by various factors, may lead to heavy traffic delay and be harmful to traffic capacity of downstream sections. Traffic incident management (TIM) systems have been developed widely to respond to traffic incidents intelligently and reduce the losses. Traffic incident response plans, as an important component of TIM, can effectively guide responders as to what and how to do in traffic incidents. In the paper, a real-time automated traffic incident response plan management system was developed, which could generate and manage traffic incident response plans timely and automatically. A web application structure and a physical structure were designed to implement and show these functions. A standard framework of data storage was also developed to save information about traffic incidents and generated response plans. Furthermore, a conformation survey and case-based reasoning (CBR) were introduced to identify traffic incident and generate traffic incident response plans automatically, respectively. Twenty-three traffic crash-related incidents were selected and three indicators were used to measure the system performance. Results showed that 20 of 23 cases could be retrieved effectively and accurately. The system is practicable to generate traffic incident response plans and has been implemented in China.